SOSIALISASI PENERAPAN AKUNTANSI PADA OBYEK WISATA D‘GONGGRES KABUPATEN LOMBOK TENGAH - Utami, Luh; Suandi, Suandi (LPPM Institut Pendidikan Nusantara Global, 2024)
This socialization program aims to provide training on the preparation of simple financial reports for the managers of the D'Gonggres tourist attraction in Central Lombok Regency. The activity is carried out through presentations and discussions. The target audience for this Community Service activity is the managers of the D'Gonggres tourist attraction in Central Lombok Regency. Through this program, it is expected that the managers will be able to optimize their cash management and begin to develop a disciplined approach to recording structured bookkeeping, enabling them to prepare simple financial reports to support operational decision-making processes. The activity begins by assisting the managers in identifying cash needs for their business operations, training them in transaction recording processes, and guiding them in the preparation of simple financial reports. The expected outcomes of this program are that the managers of the D'Gonggres tourist attraction will be able to identify cash flow and business expenses, maintain more organized bookkeeping, and eventually produce simple financial reports.